On the Reactions of Diphenyliodonium and Triphenylsulphonium Salts with Hydroxyl and 2-Hydroxy-2-Propyl Radicals - Yagci, Yusuf; Pappas, S. Peter; Schnabel, Wolfram (Walter de Gruyter GmbH, 1987)
Hydroxyl radicals react with diphenyliodonium ions, Ph2I+, and triphenylsulphonium ions, Ph3S+, in aqueous solution at room temperature with rate constants ≥ 5 x 109 l/mol s. These reactions lead to the formation of a broad transient absorption band with a maximum at ca. 370 nm, which is attributed to OH-adducts with cyclohexadienyl structures. 2-Hydroxy-2-propyl radicals react with diphenyliodonium ions in aqueous solution at room temperature with k2 = 6 x 107 l/mol s. The transient absorption band formed in this reaction has a maximum at about 390 nm and is attributed to diphenyliodo radicals, Ph2I·. In contrast, no detectable reaction occurred with 2-hydroxy-2-propylradical and triphenylsulphonium ion.